Rumen fermentation patterns in buffalo bulls fed total mixed ration supplemented with exogenous fibrolytic enzyme and/or live yeast culture - Poonooru, Ravikanth Reddy; Dhulipalla, Rinivasa Kumar; Eleneni, Raghava Rao; Kancharana, Ananda Rao (Journal of Advanced Veterinary and Animal Research, 2015)
The objective of this study was to evaluate the effect of exogenous fibrolytic enzyme (EFE) and/or live yeast culture supplementation in total mixed ration (TMR) on rumen fermentation patterns in buffalo. For this, four adult buffalo bulls weighing 377.05±43.36 kg were randomly allotted to four dietary treatments viz., TMR containing R:C ratio of 70:30 (T1), T1 supplemented with EFE at 15 g/animal/day (T2), T1 supplemented with live yeast culture at 10 g/animal/day (T3), and T1 supplemented with EFEs at 15 g/animal/day and live yeast culture at 10 g/animal/day (T4). Rumen liquor from the fistulated animals was collected at 0, 1, 2, 4, 6 and 8 h post-feeding, and was analyzed. This study revealed that rumen pH values were highest at 0 h, and were declined to minimum by 4 h post-feeding, while total volatile fatty acids (TVFA), ammonia nitrogen (NH3-N), and nitrogen (N) fractions reached to peak at 4 h post-feeding, and later followed a decreasing trend in all the treatments. Supplementation of EFE in TMR (T2) had no effect (P>0.05) on rumen pH and food and protozoal N concentration, while it influenced to increase (P<0.01) the concentration of TVFA, NH3-N and other N fractions as compared to the T1. Yeast culture supplementation in TMR (T3) increased (P<0.01) rumen pH, TVFA, NH3-N, total N, TCA-insoluble N and residual N. However, no effect (P>0.05) on food and protozoal N in buffalo bulls was found. This study indicated that, supplementation of EFE and/or live yeast culture in TMR (T4) increased (P<0.01) the rumen pH, TVFA, NH3-N and N fractions in buffalo bulls as compared to the control group. Therefore, it is concluded that supplementation of EFE and/or live yeast culture in TMR can increase the concentration of rumen metabolites in buffalo bulls. http://dx.doi.org/10.5455/javar.2015.b98